1987
DOI: 10.1002/cber.19871201107
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorverbindungen ungewöhnlicher Koordination, 211) Cycloaddition mesoionischer Verbindungen an ein stabiles Phosphaalkin – neue Möglichkeiten in der Synthese von Aza‐ und Thiaphospholen

Abstract: 1,2,3-0xadiazolium-S-olate (Sydnone) (2a -e) reagieren mit dem Phosphaalkin 1 unter [3 + 21-Cycloaddition und nachfolgender Kohlendioxid-CycloelimiNerung zu den 1 H-l,2,,CDiazaphwpholen 5n-e. Nur bei der Umsetzung 1 + 20 kann auch das Regioisomere 6 s als Nebenprodukt nachgewiesen werden. Von 1H-(bzw. 2H )-1 J,dDiazaphospholen ausgehend, sind einigc Vertrcter der gleichen Reihc durch Lithiierung und anschiicknde Methylierung zuganglich (la-c -8s-c -. ) 5n,c,e). Das 1,3-0xa-zolium-S-olat (Miinchnon) 12 sowie da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…fide (→ 14) occurs. As expected from the results with the above discussed heterophospholes, the 31 P NMR signal of the 1,3-azaphosphole 12 is shifted downfield to 106.0 ppm (∆δ = +9.4 compared to tert-butyl substitution) 19 (Table).…”
Section: [3+2] Cycloaddition Reactions With Mesoionic Compoundssupporting
confidence: 76%
See 2 more Smart Citations
“…fide (→ 14) occurs. As expected from the results with the above discussed heterophospholes, the 31 P NMR signal of the 1,3-azaphosphole 12 is shifted downfield to 106.0 ppm (∆δ = +9.4 compared to tert-butyl substitution) 19 (Table).…”
Section: [3+2] Cycloaddition Reactions With Mesoionic Compoundssupporting
confidence: 76%
“…As reported for 1a, 19 mesitylphosphaacetylene (1b) also undergoes smooth reactions with the mesoionic compounds 11 and 13 to furnish the 1,3-azaphosphole 12 or the 1,3-thiaphosphole 14; the reactions proceeding at relatively low temperatures (55°C). However, the primary formed bicyclic adducts cannot be detected: spontaneous extrusion of carbon dioxide (→ 12) or carbon oxide sul- ion peak in mass spectrum indicates that 15 is a 1:1 adduct of 1b with buta-1,3-diene.…”
Section: [3+2] Cycloaddition Reactions With Mesoionic Compoundsmentioning
confidence: 62%
See 1 more Smart Citation
“…24 It was furthermore reported that (2,2-dimethylpropylidyne)phosphane gave 3-(tert-butyl)-1methyl-1H-1,2,4-diazaphosphole 5 (R´ = Me). 25 The valence tautomer 6, which was originally postulated as a structure of sydnones in 1935 2 and as an intermediate of the aforementioned photochemical reactions, 24 was generated by a matrix photolysis. 26 Cycloadditions of sydnone imines (Z = NR) are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Other early routes to more highly substituted derivatives involve O–P replacement reactions of oxazolium salts with P(SiMe 3 ) 3 , in analogy to the first phosphinine synthesis,17 conversions of muenchnones with phosphaalkenes containing suitable leaving groups,17 or direct [3+2] cycloadditions of muenchnones or nitrilimines with phosphaalkynes,18 and – last but not least – base‐induced condensation of Bn # ‐substituted (Bn # = p ‐O 2 N‐C 6 H 4 ‐CH 2 ‐) CH‐acidic ketene‐aminals p TolCH=CH(NR 2 )NBn # Ph with PCl 3 . 1,3‐Oxaphospholes and 1,3‐thiaphospholes have been obtained by analogous condensations with OBn # ‐ and SBn # ‐substituted ketene aminals,19 reactions of t BuC≡P with arylmethoxycarbene Cr(CO) 5 complexes, with α,α′‐diketo‐diazo compounds or with isomuenchnones formed from them,20 and with 1,3‐dithiolium‐4‐olates,17b,18a,21 respectively. All of these syntheses have previously been reviewed in detail and are mentioned here only briefly 4,5a,5b,9.…”
Section: Recent Syntheses and New Types Of Electron‐rich Heterophomentioning
confidence: 99%